2021
DOI: 10.1002/hep.31535
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide Association Study and Meta‐analysis on Alcohol‐Associated Liver Cirrhosis Identifies Genetic Risk Factors

Abstract: 25,26,28 **, for the GenomALC ConsortiumBaCKgRoUND aND aIMS: Only a minority of heavy drinkers progress to alcohol-associated cirrhosis (ALC). The aim of this study was to identify common genetic variants that underlie risk for ALC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 53 publications
(95 reference statements)
0
74
1
1
Order By: Relevance
“…3 Recently, a common coding variant (MTARC1 p.Ala165Thr) was reported to be associated with protection against NAFLD and its progression, [4][5][6] as well as protection from alcohol-related and all-cause cirrhosis. 7,8 Other reports indicated that NAFLD severity was reduced in MTARC1 p.Ala165Thr carriers. 9,10 MTARC1, the mitochondrial amidoxime-reducing component 1 gene, encodes the mitochondrial amidoxime-reducing component, which is involved in metabolic processes in the liver (e.g., activating N-hydroxylated prodrugs or reducing nitrite to produce nitric oxide).…”
Section: Context and Significancementioning
confidence: 99%
“…3 Recently, a common coding variant (MTARC1 p.Ala165Thr) was reported to be associated with protection against NAFLD and its progression, [4][5][6] as well as protection from alcohol-related and all-cause cirrhosis. 7,8 Other reports indicated that NAFLD severity was reduced in MTARC1 p.Ala165Thr carriers. 9,10 MTARC1, the mitochondrial amidoxime-reducing component 1 gene, encodes the mitochondrial amidoxime-reducing component, which is involved in metabolic processes in the liver (e.g., activating N-hydroxylated prodrugs or reducing nitrite to produce nitric oxide).…”
Section: Context and Significancementioning
confidence: 99%
“…The protective role of UBXN3B in these disease conditions in mice may be potentially applicable to those in humans considering that the UBXN3B protein is highly conserved in mammals (98% identity between human and rodent protein). Importantly, an rs374702773 (delta T allele in intron) in UBXN3B is associated with protection against alcoholic liver cirrhosis, a chronic inflammatory condition in humans 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of single nucleotide variants rs738409 in PNPLA and rs58542926 in transmembrane 6 superfamily member 2 (TM6SF2) associate with the risk of hepatocellular carcinoma, whereas variant rs4607179 of hydroxysteroid 17-beta dehydrogenase (HSD17B13) reduces the risk [213]. In a genome-wide association study, variants rs738409 of PNPLA and rs4607179 of HSD17B13 show significant association with the appearance of alcohol-associated liver cirrhosis, and rs374702773 of Fas-associated factor family member 2 (FASF2) shows a protective association [206].…”
Section: Gene Variantsmentioning
confidence: 99%